Cadernos de normalistas e a sistematização do saber profissional para ensinar aritmética no curso primário, na década de 1950 - Giusti, Bruna Lima Ramos [UNIFESP] (2020)
The present study addresses the systematization of the professional knowledge of the teacher who will teach arithmetic in the primary course in the 1950s, in Brazil. This study is part of the Thematic Project entitled “Mathematics in Teacher Education and Teaching: processes and dynamics of the production of professional knowledge, 1890-1990”, financed by FAPESP, of wider scope, which aims to answer the questions: “how are produced, systematized and institutionalized the professional knowledge of the teacher who teaches mathematics?” and "how to characterize mathematics as a professional teaching knowledge?”. The present study focuses specifically on the systematization of professional knowledge to teach arithmetic in primary school in the 1950s, in Brazil. Based on the studies on teacher education characterized by Hofstetter and Schneuwly (2017), a guiding question for this research was elaborated, expressed as: what elements can be extracted from the analysis of the notebooks of normalists that configure a professional knowledge of the teacher who will teach arithmetic in the 1950s? The study presents an analysis of three notebooks of normalists of that time, called Golden Years, and with that, it was possible to evidence elements of a specific knowledge of the teacher who would teach arithmetic in the first school years. For the analysis, we used a research methodology described by Lima and Valente (2019), referenced in the studies of Peter Burke (2016), which consists of work steps given by: compilation of teaching experiences, comparative analysis of notebooks and systematization teaching knowledge. With that, it was possible to extract from the notebooks elements that composed an arithmetic to teach and an arithmetic for teaching, configuring a relationship between these knowledges and establishing the nature of professional knowledge for the teacher who teaches arithmetic in the primary course in the 1950s. This research was concluded by presenting elements that constitute this professional knowledge, starting from a relationship between arithmetic to teach and arithmetic for teaching.